An introduction to the policy process : theories, concepts, and models of public policy making. (3rd ed.) - Birkland, Thomas A. (Taylor and Francis, 2020)
This book is organized in three broad sections. This chapter and chapters 2 and 3 are overviews of the policy process and of the environment in which policy is made. Chapter 3 introduces the stages model of the policy process, which serves to organize the various parts of the process so that we can analyze them. Chapters 4 and 5 are about the actors in the policy process. Chapters 6 through 9 cover the outputs and processes of public policy. Chapter 10 brings all this together by considering modern, better theories of the policy process that improve upon the stages model and develop better grounded theories.